REPLACING FISH MEAL BY CANOLA MEAL AND SUPPLEMENTING WITH PHYTASE AND CITRIC ACID FOR IMPROVING MINERAL DIGESTIBILITY IN Cirrhinus mrigala FINGERLINGS - Muhammad Zubair-ul-Hassan Arsalan; Syed Makhdoom Hussain; Nisar Ahmad; Bilal Ahmad; Zeeshan Yousaf; Muhammad Faisal; Adan Naeem (Journal of Animal and Plant Sciences, 2024)
The purpose of this study was to analyze how the mineral digestibility of Cirrhinus mrigala was improved by the replacement of canola meal (CM) along with the supplementation of citric acid (CA) and phytase (PHY). A 90-day feeding trial was conducted in a completely randomized design. Sixteen test diets were formulated with different concentrations of CM (0%, 25%, 50%, and 75%), in the basal diet. Each concentration level was supplemented with four doses, one without supplementation, second with 2.5% CA, third with 750 FTUkg-1 PHY and fourth with combined supplementation (CA + PHY) to form sixteen test diets (T1-T16). Fifteen fingerlings (N = 720) were kept in each tank in triplicate. At the end of the trial, it was revealed that as the amount of CM in the diets increased, there was a significant (P≤0.05) increase in mineral digestibility (Fe, Ca, Mg, K, Mn, Cu, P, Na, Cr, Zn and Al). The fish that consumed 50% CM-based diet supplemented with 2.5% CA and 750 FTUkg-1 PHY had the maximum apparent digestibility coefficient of minerals (K 73.76%, Ca 64.79%, Na 62.56%, P 73.11%, Cu 76.52%, Fe 77.14%, Mn 71.87%, Mg 71.42%). The results of this research suggest that supplementing a diet high in CM (50%) with 2.5 percent CA and 750 FTUkg-1 PHY is the most effective strategy to increase the digestibility of minerals in C. mrigala fingerlings.
Keywords: Fish meal; substitution; aquaculture; plant meal; acidified phytase